2019
DOI: 10.1158/1078-0432.ccr-19-0289
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparison of GITR Expression in Solid Tumors

Abstract: Purpose: Determine the differential effect of a FcgR-binding, mIgG2a anti-GITR antibody in mouse tumor models, and characterize the tumor microenvironment for the frequency of GITR expression in T-cell subsets from seven different human solid tumors.Experimental Design: For mouse experiments, wild-type C57BL/6 mice were subcutaneously injected with MC38 cells or B16 cells, and BALB/c mice were injected with CT26 cells. Mice were treated with the anti-mouse GITR agonist antibody 21B6, and tumor burden and survi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…GITR is constitutively expressed in Treg cells and is critical for the development and activity of Treg cells ( 2 , 8 , 25 ). The expression of GITR in Tregs can be up-regulated after activation or in tumor microenvironment, and the level of GITR usually positively correlates with the immunosuppressive function of Tregs ( 26 , 27 ). GITR engagement in Treg cells can have multiple distinct effects.…”
Section: Effect Of Gitr On Treg Cellsmentioning
confidence: 99%
“…GITR is constitutively expressed in Treg cells and is critical for the development and activity of Treg cells ( 2 , 8 , 25 ). The expression of GITR in Tregs can be up-regulated after activation or in tumor microenvironment, and the level of GITR usually positively correlates with the immunosuppressive function of Tregs ( 26 , 27 ). GITR engagement in Treg cells can have multiple distinct effects.…”
Section: Effect Of Gitr On Treg Cellsmentioning
confidence: 99%
“…34 Vence et al confirmed that tumours with high expression of CD8 + and CD4 + , after GITR mAb treatment, have the better response, mainly lung cancer, renal cancer and melanoma. 25 Moreover, preliminary results showed a better suppression of tumour growth with intratumour compared with intravenous injection. In fact, the intratumour injection was able to induce a systemic antitumour immune reaction, exerting its effect on injected and on un-injected tumours.…”
Section: Modulation Of Gitr In Preclinical Tumour Models Antitumour Amentioning
confidence: 99%
“…[21][22][23][24] Importantly, GITR is not expressed on the tumour itself, but it is expressed on tumour-infiltrating lymphocytes (TILs) of several human cancer types including lung cancers, renal cell carcinoma, head and neck carcinoma and melanoma. 25 The most widely used molecules to trigger GITR are agonist antibodies like DTA-1 (a rat IgG2b) 5 or recombinant version of GITRL, like GITR-Fc.…”
Section: Modulation Of Gitr In Preclinical Tumour Models Antitumour Amentioning
confidence: 99%
See 2 more Smart Citations